2017
DOI: 10.1007/s11192-017-2500-1
|View full text |Cite
|
Sign up to set email alerts
|

Product and process innovation in manufacturing firms: a 30-year bibliometric analysis

Abstract: -Built upon a thirty-year dataset collected from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 93 publications
2
54
0
4
Order By: Relevance
“…Bibliometric methods have been widely and increasingly used to provide a comprehensive map of the knowledge structure in a given field (Kraus, 2011;Kraus et al, 2012Kraus et al, , 2014L opez-Fernández et al, 2016;Xi et al, 2015) or in a given journal (Laudano et al, 2018;Marzi et al, 2017). A mixed methods bibliometric investigation of the World Review of Entrepreneurship, Management and Sustainable Development: From qualitative to quantitative data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric methods have been widely and increasingly used to provide a comprehensive map of the knowledge structure in a given field (Kraus, 2011;Kraus et al, 2012Kraus et al, , 2014L opez-Fernández et al, 2016;Xi et al, 2015) or in a given journal (Laudano et al, 2018;Marzi et al, 2017). A mixed methods bibliometric investigation of the World Review of Entrepreneurship, Management and Sustainable Development: From qualitative to quantitative data.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, bibliometric studies have shown their usefulness in a broad range of fields such as management (Podsakoff et al, 2008), entrepreneurship (Landström et al, 2012;Laudano et al, 2018), operations management (Chen and Hsu, 2009;Zhu et al, 2015) and innovation (Fagerberg et al, 2012;Appio et al, 2016;Marzi et al, 2017) by helping scholars to sort the streams of research from the "tangled forest" of scientific proliferation. Following Brown and Eisenhardt (1995) and Furrer et al (2008), this paper aims to help scholars to better understand the direction in which the field is going and where the gaps are, thus providing a guideline for scholars in positioning their future research focussing on two questions.…”
Section: Introductionmentioning
confidence: 99%
“…In TIM field, Randhawa, Wilden, and Hohberger (2016) conducted a bibliometric review of open innovation to reveal three distinct areas, the first of which were fully investigated and the other two remained relatively underresearched. Bibliometric reviews about green innovation, national innovation, product and process innovation, and innovation system are also provided by scholars (Liu, Yin, Liu, & Dunford, 2015;Marzi, Dabić, Daim, & Garces, 2017;Schiederig, Tietze, & Herstatt, 2012;Sun & Grimes, 2016). The most related bibliometric reviews are those treating TIM as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Process innovations concern new production processes or technologies. This study, like many other process innovation studies (Krzeminska and Eckert, 2015;Marzi et al, 2017), focused on new material, equipment or reengineering of operational processes. In doing so, concern stemmed from the conditions that may determine the choice of a decision-making approach.…”
Section: Limitations and Future Researchmentioning
confidence: 99%